PEMANFAATAN MEDIA SOSIAL SEBAGAI MEDIA KOMUNIKASI WISATA REKLAMASI LAHAN BEKAS TAMBANG DI KABUPATEN BANGKA - Ferdiana, Ferdiana (KOMUNIKASIA: Journal of Islamic Communication and Broadcasting, 2021)
The condition of the ex-tin mine excavated land greatly affects environmental conditions because it destroys the ecosystem. The reclamation efforts carried out by PT. Timah, Tbk in the form of new tours in the form of reclamation tours of ex-mining land, namely is Kampung Reklamasi Air Jangkang Merawang and Perkebunan Air Nyatoh. This new tour needs to be disseminated in order to provide an understanding for the community about the use of ex-mining land. So social media is one of the most effective and efficient media to do this. This study is a qualitative research with a descriptive approach that will explain the use of social media as a communication medium for tourism reclamation of ex-mining land in Bangka Regency. The results of the study found that the social media used by PT. Timah, Tbk in the communication of ex-mining land reclamation tourism in Bangka Regency included YouTube, Facebook, Instagram, Twitter and online news portals. The most dominant social media used is the Facebook account of PT. Timah, Tbk. PT. Timah, Tbk utilizes social media to communicate the application of the 4 E concept; Education, Ecology, Environment, Economy.